LINGUISTOCULTURAL ANALYSIS OF CRAFTSMANSHIP LEXICAN - Gulmira Ergasheva Bakhrom qizi (Prospects for innovative technologies in science and education, 2025)
In the article, it is a fact that language is a diverse phenomenon, its possibilities are unlimited, its national-cultural features are studied in the field of linguistic-cultural studies, and it is interconnected with the field of handicrafts, which is considered an important link of society and contains national values and traditions, all these are analyzed through materials. Paraphrases related to sewing, embroidery, and goldsmithing are given, and information about these types of industries is provided.